1994
DOI: 10.1016/0735-1097(94)90278-x
|View full text |Cite
|
Sign up to set email alerts
|

Task force 1: The underserved

Abstract: The ACC has affirmed its commitment to universal access to health care. Underserved populations exist in urban and rural centers. Common to each is a paucity of personnel trained in cardiovascular care and a lack of access to preventive and highly technologic services. These factors contribute to a poor health outcome (75). Part of the rural problem can be corrected by the transfer of information to local providers by the use of new information systems. Included would be real-time electronic consultation, on-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…4). Recent observational results suggest that the IMF has indeed a universal Salpeter slope at the upper end and that any variability should be confined to the lower end (Haywood 1994, Meyer et al 1999). Contrary to the Salpeter IMF which raises monotically with decreasing stellar mass, the current observed IMF in the solar neighbourhood may be roughly flat at the lower end or even may peak at a mass around 0.25M ⊙ and decline into the brown dwarf regime.…”
Section: The Shape Of the Imf In A Metal Deficient Mediummentioning
confidence: 99%
“…4). Recent observational results suggest that the IMF has indeed a universal Salpeter slope at the upper end and that any variability should be confined to the lower end (Haywood 1994, Meyer et al 1999). Contrary to the Salpeter IMF which raises monotically with decreasing stellar mass, the current observed IMF in the solar neighbourhood may be roughly flat at the lower end or even may peak at a mass around 0.25M ⊙ and decline into the brown dwarf regime.…”
Section: The Shape Of the Imf In A Metal Deficient Mediummentioning
confidence: 99%
“…Andersen 2002Andersen , 1991Bahcall & Soneira 1980;Chiappini et al 1997;Bruzual & Charlot 2003;Bruzual A. & Charlot 1993;Haywood 1994;Matteucci 2009;Popper 1997;Hernandez et al 2000;Portinari & Chiosi 2000;Ribas et al 2000a,b, for representative works in the quoted fields).…”
Section: Analytical Relationsmentioning
confidence: 99%
“…However, Kuijken & Gilmore (1989) derived a scale height of 249 pc for the old-disk stars. Haywood (1994) showed, from an analysis of numerous star counts towards the pole using his self-consistent evolutionary model, that the thin disk scale height does not exceed 250 pc. Ojha (1999) also found that the scale height of the thin disk is 240 pc based on an analysis of two star count samples.…”
Section: Density Distribution In the Diskmentioning
confidence: 99%